2016
DOI: 10.1007/s10064-016-0962-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical impact of construction of the western section of the Hallandsås rail tunnel in Sweden

Abstract: This paper presents a study of the hydrochemical changes that took place during construction of a section of the Hallandsås rail tunnel in southwest Sweden based on monitoring from spring 2011 to summer 2012. Leakage into the tunnel during construction caused lowering of the groundwater levels, which in turn resulted in a decrease in or absence of base flow in the streams. The water in the streams became dominated by meteoric water during the drawdown periods. Meanwhile, wetlands were aerated, and oxygen could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Piña et al modeled the path of surface water into the tunnels using hydrochemical analyses and isotopic techniques and found that the depth of burial of the tunnels affects the intensity and timing of water-rock action and that carbon dioxide and oxygen in the air react with the exposed minerals [4]. This type of alteration of the dissolution state of minerals due to the renewal of aquifers by tunnel drainage, resulting in hydrogeochemical imbalances, is common in all types of rock formations [5]. The impact on water quality and water chemistry is even more pronounced if the tunnel passes directly through underground karst aquifers and fracture zones [6].…”
Section: Introductionmentioning
confidence: 99%
“…Piña et al modeled the path of surface water into the tunnels using hydrochemical analyses and isotopic techniques and found that the depth of burial of the tunnels affects the intensity and timing of water-rock action and that carbon dioxide and oxygen in the air react with the exposed minerals [4]. This type of alteration of the dissolution state of minerals due to the renewal of aquifers by tunnel drainage, resulting in hydrogeochemical imbalances, is common in all types of rock formations [5]. The impact on water quality and water chemistry is even more pronounced if the tunnel passes directly through underground karst aquifers and fracture zones [6].…”
Section: Introductionmentioning
confidence: 99%